PHYTOCHEMICAL SCREENING AND ANTIOXIDANT ACTIVITY OF RED FLOWERED MIRABILIS JALAPA LEAF IN DIFFERENT SOLVENTS - P. SELVAKUMAR; DEVI KANIAKUMARI; V. LOGANATHAN (International Journal of Pharma and Bio Sciences, 2012)
The present phytochemical study investigates about red flowered Mirabilis jalapa leaf in different extracts using acetone, ethyl acetate, ethanol and petroleum ether solvents. From the crude extracts various parameters of pharmacognostical standards such as ash and extractive values, microscopical characters of leaf powder were determined. The village people of India use this plant to cure many infirmities including dysentery, diarrhea and muscular pain. Further, the qualitative phytochemical screening of ethanolic extract of red flowered plant leaf reveals the presence of tannins, alkaloids, carbohydrates, terpenes and saponins. Moderate amount of glycosides were also observed. Acetone extract of plant leaf showed the presence of alkaloids, carbohydrates. Ethyl acetate extract of plant leaf showed the presence of alkaloids, carbohydrates and glycosides. Petroleum ether extract of plant leaf showed the presence of alkaloids. The research indicated clearly that red flowered Mirabilis jalapa plant has strong antibacterial potential and is active against a wide range of microorganisms. The observed antibacterial activities were believed to be due to the presence of phytochemical actives. We have further characterized some pharmacological properties of ethanolic extract of leaf. Therefore, we intend to contribute to understand the pharmacological effects and clarify the complex use of this medicinal plant. The results of the present study led us to the inference that the plant extract possesses modest medicinal and antioxidant properties. Further studies are necessary to identify the exact active compounds within the extract and to elucidate the mechanism of action.